UDK iOS game development beginner's guide : create your own third-person shooter game using the Unreal Development Kit to create your own game on Apple's iOS devices, such as the iPhone, iPad and iPod Touch /: create your own third-person shooter game using the Unreal Development Kit to create your own game on Apple's iOS devices, such as the iPhone, iPad and iPod Touch. (2012) - Unknown
No abstract available